Determination of Water-Soluble and Fat-Soluble Vitamins in Margarines Marketed in Nigeria - Odidika , Collins Chibuzor; Okoye, Patrice-Anthony Chudi; Ijeoma Nnabude, Chinelo (Indonesian Journal of Green Chemistry, 2025)
This study involved the determination of water-soluble and fat-soluble vitamins in margarines marketed in Nigeria. The vitamin content was quantified using UV-visible spectrophotometer along with standard procedures. The results obtained showed vitamins A, D, E, B (1,2,3,6 and 12), and C were detected in most of the samples analyzed, and the most predominant vitamin in all the margarine samples was vitamin E, which ranged from 2.03-3.45 mg/100g, with sample M3 having the least content, and sample M7 having the highest content, the second most predominant vitamin was vitamin C, ranging from 0.75-1.42 mg/100g, with sample M6 having the least content and sample M1 having the highest content. The other vitamins were in the following ranges: vitamin A (0.00-0.46 mg/100g), D (0.02-0.13 mg/100g), B1 (0.006-0.032 mg/100g), B2 (0.012-0.023 mg/100g), B3 (0.39-0.66 mg/100g), B6 (0.18-0.33 mg/100g), and B12 (0.00-0.14 mg/100g). The most common vitamin in all the margarine samples was vitamin E, ranging from 2.03 to 3.45 mg/100g. Sample M7 had the highest content and also provided the most overall vitamins, followed by sample M1, which had the highest levels of vitamins C, , and . These findings suggest that Nigerian margarines contain significant amounts of vitamins, especially vitamins E and C, and may provide a small boost to dietary vitamin intake.